Évaluation de la Satisfaction des Patients aux Techniques Thérapeutiques dans le Service des Brûlés de l'Hôpital Militaire d'Instruction Mohammed V - Une Étude Exploratoire - Kossai Housni (Darul Yasin Al Sys, 2026)
This exploratory study aims to analyze the relationship between patient satisfaction and therapeutic practices within the burn unit of the Mohammed V Military Instruction Hospital in Rabat. Framed within the field of health psychology, it focuses on care perception, communication quality, and healthcare staff competence. Using both qualitative and quantitative approaches, 10 patients, 10 doctors, and 10 nurses were surveyed through questionnaires on satisfaction, working conditions, and quality of care. The findings indicate a generally high level of patient satisfaction, mainly associated with staff competence and the quality of caregiver-patient interactions. However, aspects such as communication and administrative management require improvements. The discussion highlights the importance of recognition, empathy, and psychosocial support in Moroccan healthcare institutions.